PLACE ATTACHMENT AND PRO-ENVIRONMENTAL BEHAVIOUR PARALYSIS: A STUDY OF HOUSEHOLD SOLID WASTE MANAGEMENT - Hope Iyawe (Journal of Construction Project Management and Innovation)
Solid waste management (SWM) in most developing countries has been a source of worry for city managers and concerned residents as heaps of refuse that dot the cityscape has increase drastically and become unsightly, thereby creating the impression that concerted efforts have not been made to address the situation. Various studies undertaken in most developed countries have consistently shown that there exists a strong correlation between place attachment (PA) and pro-environmental behaviour (PEB). One of the implications of this strong correlation is that household solid waste (HHSW) have been successfully managed. While individuals residing in cities of developing countries in places such as Nigeria are known to have strong PA, contemporary literature suggests that this nexus has not impacted positively on how HHSW has been managed. In this context, therefore, a disconnect exists between the two experiences. Drawing on recent fieldwork conducted in Urora, Benin City in Nigeria, which employed both ethnographic-based observation approach and the principles of participatory research, this study sought to understand the causal factors responsible for the disconnect between PA and PEB that continue to facilitate the indiscriminate disposal of HHSW. The result suggests that factors like: (1) strong PA exhibited by residents serve only social and personal interests that can hardly translate to PEB (2) with the indigenes out-numbered by the ‘visitors’ coupled with the belief that the ‘visitors’ have a home elsewhere, cooperation and oneness among residents is not guaranteed; and, (3) given the wet season of seven months coupled with lack of drainage facilities and results in submergence this situation encourages non-challant behaviours towards waste management as the area is almost degraded, forsaken and abandoned. These issues are explored within the wider theoretical debates involving PA and PEB from a developing world context.